Analisis Faktor-faktor yang Mempengaruhi Pilihan Perusahaan Terhadap Akuntansi Konservatif - Widya Widya (The Indonesian Journal of Accounting Research, 2013)
The objective of this study is to investigate what factors influence firms selection of conservative accounting. The proposed hypotheses are: (1) The higher the firms ownership structure of the capital, the more likely the firms select a conservative accounting strategy, (2) The higher the frequency of the debt covenant abrogation, the more likely the firms select a less conservative accounting strategy, (3) The bigger expended political cost, the more likely the firms select a more conservative accounting strategy, and (4) Growing companies are more likely to select a more conservative accounting.The samples of the study are the manufacturing firms listed in Jakarta Stock Exchange. The data are collected using targeted sampling method. The number of the firms serving as the samples is 74 in 1995-2002.The results of the study indicate that in general Indonesian firms select conservative accounting method (76.9%). The influencing factors of the selection of the method are ownership structure, political cost and growth, while the debt covenant with the proxy of leverage is not the factor influencing the firms choice of it because the contract rarely takes place in the country.There are three conservative accounting proxies as suggested by Watts (2003), i.e. earning stock return relation measures, earnings accrual measures, and net asset measures. The study formulates assumed model based on the PSAK no. 14 (on stock), 17 (on depreciation), 19 (on amortization) and 20 (on R&D cost) to determine if the firms select conservative or optimistic accounting. Sensitivity analysis is made in the study to see the conservative proxy (Watt, 2003), which fits to the assumed model using t-test comparison coefficient across regression. Based on the results of the study, the net asset measures are the proxies that are appropriate to the assumed model proxy.